Réponses

2014-10-09T10:14:07+02:00
A=7/9 - 1/9 x 3/2
  =7/9 - [(1 x 3) / ( 9 x 2 )]
  =7/9 - 1/6
  =[(7 x 6 ) - (9 x 1)] / (9 x 6)
  =(42 - 9) / 54
  =33/54
A=11/18

B=5/2 : ( 7/4 + 9/2)
  =5/2 ; [7 + (9 x 2)] / 4
  =5/2 : ( 7 + 18) /4
  =5/2 : 25/4
  = 5/2 x 4/25
 B =2/5
Meilleure réponse !
2014-10-09T10:21:42+02:00
Bonjour

tu commences par la multiplication

A = 7/9 - 3/18
tu mets au même dénominateur

A = 14/18 -3/18 = 11/18

B = 5/2 : (7/4 + 18/4)
B = 5/2 : 25/4
B = 5/2 x 4/25 = 20/50 = 2/5